РАЗВИТИЕ ЧИТАТЕЛЬСКОЙ КОМПЕТЕНЦИИ У СТУДЕНТОВ ОБУЧАЮЩИХСЯ В ВУЗе - Салихова, З.А. (SCIENCE and SOCIETY, 2022)
The article, that a modern process is currently taking place in Uzbekistan, a change in the target orientation, from the socialization of the individual to its formation, has led to the use of such a category as education. Previously, students had to have a certain set of knowledge, skills, but now a new criterion for measuring learning outcomes is competence.